1969
DOI: 10.1039/c29690001298
|View full text |Cite
|
Sign up to set email alerts
|

Curtius-type rearrangement of a sulphonyl azide

Abstract: Six products have been identified from the thermolysis of mesitylene-2-sulphonyl azide in dodecane : two are derived from a Curtius-type rearrangement of the corresponding sulphonyl nitrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The present matrix isolation study on CF 3 SO 2 N 3 will contribute to the understanding of the fundamental chemistry of sulfonyl azides and helps to understand their complicated photochemistry in solution, which for a long time have impaired the broader application of sulfonyl azides as the nitrene precursor. The distinct photodecomposition and thermal decomposition of the sulfonyl azides CF 3 SO 2 N 3 and FSO 2 N 3 , and the surprisingly different reactivity of the corresponding sulfonylnitrenes certainly demand further systematic theoretical studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present matrix isolation study on CF 3 SO 2 N 3 will contribute to the understanding of the fundamental chemistry of sulfonyl azides and helps to understand their complicated photochemistry in solution, which for a long time have impaired the broader application of sulfonyl azides as the nitrene precursor. The distinct photodecomposition and thermal decomposition of the sulfonyl azides CF 3 SO 2 N 3 and FSO 2 N 3 , and the surprisingly different reactivity of the corresponding sulfonylnitrenes certainly demand further systematic theoretical studies.…”
Section: Discussionmentioning
confidence: 92%
“…Sulfonyl azides, RSO 2 N 3 , are important reagents in synthetic chemistry. Similar to the reactions of related carbonyl azides, , both photodecomposition and thermal decomposition reactions of sulfonyl azides have been extensively studied in solution. The intervention of sulfonylnitrenes, RSO 2 N, were chemically inferred from secondary decomposition products. A number of triplet sulfonylnitrenes have already been experimentally detected among the photolysis products of the corresponding azides by electron paramagnetic resonance (EPR) spectroscopy at low temperatures. These early studies strongly suggested that sulfonylnitrenes adopt triplet ground states, and no straightforward evidence for a Curtius-type rearrangement was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Provided that this photo‐rearrangement can be transferred to the analogous sulfonyl nitrenes, R S(O) 2 N, it would give access to sulfinyl nitrites, R S(O)NO. However, although the chemistry of sulfonyl nitrenes has been known for nearly a half century,1519 spectroscopic studies on these intermediates are very limited. Low‐temperature EPR studies have established their triplet ground state nature,20,21 and a transient UV absorption band at 325 nm was attributed to 4‐methylbenzenesulfonyl nitrene in cyclohexane at 77 K 20.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐temperature EPR studies have established their triplet ground state nature,20,21 and a transient UV absorption band at 325 nm was attributed to 4‐methylbenzenesulfonyl nitrene in cyclohexane at 77 K 20. It was claimed, that the Curtius rearrangement of sulfonyl nitrenes, R S(O) 2 N, yield unstable N‐sulfonyl imides, R N=SO 2 [Equation (3)] 15,19…”
Section: Introductionmentioning
confidence: 99%
“…With 2-methylbenzenesulfonyl azide (4), the intramolecular insertion product, benzylsultam (5), was obtained in 21% yield from gas phase thermolysis in the absence of benzene and in 13% yield with benzene present. This result is readily explained in terms of a sulfonylnitrene intermediate which inserts into the adjacent methyl group.…”
mentioning
confidence: 99%